Optimisation and thermo-mechanical analysis of a coated steam dual pipe system for use in advanced ultra-supercritical power plant. (September 2020) - Guo, X.F.; Benaarbia, A.; Sun, W.; Becker, A.; Morris, A.; Pavier, M.; Flewitt, P.; Tierney, M.; Wales, C.
Abstract: Improving the energy efficiency of power plants by increasing steam operating temperature up to 700 °C can be achieved using novel engineering design concepts such as coated steam pipe systems. This paper presents an optimised design for a novel coated dual pipe system to be used in advanced ultra-supercritical power plant. The approach developed in this study uses a combination of an optimisation algorithm and FE simulation, based on the reduction of the hoop stress at top coat/bond coat interface generated by the thermal and mechanical stresses. This allows determination of the optimum dimensions and material properties of the system. A unified viscoplastic model which combines a power flow rule with non-linear anisothermal evolution of isotropic and kinematic hardening has been used for the thermo-mechanical analysis of the coated dual pipe system under the cyclic loading. The results of the optimisation show that the value of the hoop stress at the top coat/bond coat interface is reduced significantly, compared with that in the baseline model. Finally, the potential technical challenges and future works for the proposed steam dual pipe system are discussed. Graphical abstract: Image 1 Highlights: A combination of an optimisation algorithm and FE simulation is developed to determine the optimum dimensions and material properties of the coated dual pipe system. An analytical optimisation Algorithm is introduced. A unified viscoplastic model is used for the thermo-mechanical analysis of the system under the cyclic loading.